Next-Generation Sequencing in Plant Breeding: Challenges and Possibilities - Kayıhan, Ceyhun; Yilmaz, Hikmet; Özden Çiftçi, Yelda (Springer International Publishing, 2023)
The next-generation sequencing (NGS) is increasingly becoming one of the popular areas which provides great opportunities to understand and design genetic makeup and behavior of plant genomes. NGS is devised into two categories as second-and third-generation sequencing. The second-generation technologies which require the preparation of amplified sequencing libraries may not only reduce sequencing costs but also increase the speed of sequencing with maintaining high accuracy. However, the read length of these technologies is shorter than the first generation. Although the technologies of third-generation sequencing have generated the longer reads than second-generation sequencing, their data have relatively higher error rates than first-and second-generation technologies. However, NGS technologies are still undergoing development, and it is expected to be improved for error rates, accuracy, and time. These technologies opened a new era in genomics and molecular biology of many organisms including plants where they have been used to enhance the quality of nutrition in products for a variety of several human activities such as food, feed, fuel, shelter, landscaping, and eco-system services. When NGS technologies are used to generate whole genome sequences, transcriptome sequencing, and exome sequencing for a wide variety of crops, these technologies will provide more effective and rapid tools to determine the genetic basis of agriculturally desired traits and to estimate the breeding value of individuals of each plant species. Also, NGS technologies generate huge amounts of sequenced data that make it possible to profile nucleotide variation and large-scale discovery of functional markers that may aid to select important traits. NGS analyses for plant breeding have huge advantages and opportunities but demand low cost, and more efficient, high-throughput genotyping for screening large populations will be obtained within lesser time. All of these advances and challenges of NGS will be discussed in this chapter with providing an overview of the major NGS platforms and their impact and applications in plant breeding together with the bioinformatics utilized for NGS data analysis. © 2024 Elsevier B.V., All rights reserved.
Keywords: 454 technology; Epigenesis; Genetic markers; Genome databases; Illumine technology; Ion torrent technology; Next-generation sequencing